Impact Of a Planned Focused On Form Approach Used to Teach Grammar Structures With Efl a2 Learners: Action Research With Public University Students - Espol (2017)
Teaching a second language means developing communicative skills. Along with it, communication demands accuracy and efficiency at the time of expressing ideas, sharing opinions and providing information. however, at the time of speaking, the speaker and the receptor, whose mother tongue is not english, misunderstand the messages due to the lack of grammatical structures acquaintance. With the aim of improving efl students´ knowledge of grammatical features, a methodology called planned focus on form, was applied within a group of 30 learners. This study took place in a public ecuadorian institution, during six sessions. each session was oriented to a particular grammatical structure: simple present, present continuous, present perfect, simple past, will-won´t ands going to respectively. chapter one provides the context where the study took place, the student´s background, the objectives and ethical considerations.